Rural Tourism In Malaysia: Towards Sustaining The Local Economy - Hassan, Fatimah; Badarulzaman, Nurwati; Hj. Ali, Kausar (Pearson Prentice Hall, 2006)
With the decline in agricultural productivity and other rural employment sectors, many rural areas worldwide have moved towards tourism as a strategy to boost their waning economy. A combination of factors has propelled the trend towards rural tourism including the anxieties of urban lifestyles, interest in cultural heritage and cultural roots, improved transportation and communication systems, increases environmental consciousness and nature appreciation.